Pengaruh Budaya Perusahaan Solid, Safe, Speed, Smart, Inovation (S4I) dan Gaya Kepemimpinan Terhadap Semangat Kerja Karyawan Departemen Integrated Slab Yard di PT. Krakatau Argo Logistics - Muyasaroh Muyasaroh (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
ANDI FIRMANSYAH, NPM : 1902011093, “The Influence of Solid, Safe, Speed, Smart, Innovation (S4I) Corporate Culture and Leadership Style on the Work Spirit of Integrated Slab Yard Department Employees at PT. Krakatau Argo Logistics” thesis Management Study Program Faculty of Economics and Business Al-Khairiyah University under the guidance of Muyasaroh, S.E., Sy., M.E and M. Fulaisum Firdaus, S.E., M.M. 1). How does corporate culture (S4I) influence the work spirit of Integrated Slab Yard Department employees at PT. Krakatau Argo Logistics? 2) How does leadership style influence the work spirit of Integrated Slab Yard Department employees at PT. Krakatau Argo Logistics? 3) How does corporate culture (S4I) and leadership style influence the work spirit of Integrated Slab Yard Department employees at PT. Krakatau Argo Logistics?. This aims to determine the Influence of Solid, Safe, Speed, Smart, Innovation (S4I) Corporate Culture and Leadership Style on Employee Work Spirit in the Integrated Slab Yard Department at PT. Krakatau Argo Logistics, this study uses quantitative data by distributing questionnaires to respondents, namely Employees of PT. Krakatau Argo Logistics with a population study of 66 samples 66 with saturated sampling techniques. The reliability testing technique uses the Cronbach Alpha technique with hypothesis testing using the Person Product Moment correlation at a significant level of a = 5%. Based on data processing from SPSS version 25, the results of the analysis on the coefficient show that the r2 value is 0.621 and is stated in the strong category. The formula for the determination coefficient KD = r2 x 100% so that the determination coefficient value KD = 0.6212 X 100% = 38.5%. So it can be concluded that the variables X1 (Corporate Culture) and X2 (Leadership Style) and Y (Employee Work Spirit) have a relationship of 38.5 or rounded up to 38.5%.